DEVELOPMENT, EFFICACY AND COMPERATIVE ANALYSIS OF NOVEL CHICKPEA BASED READY-TO-USE THERAPEUTIC FOOD - J. U. Hassan; S. Iqbal; N. Naeem; Frasat; M. Nasir (Journal of Animal and Plant Sciences, 2016)
The development of ready-to-use therapeutic foods (RUTF) using indigenous sources in under developing countries is highlgy required. In the present study, chickpea based RUTF was prepared, analyzed and evaluated for true digestibility (TD), net protein utilization (NPU), biological value (BV), protein efficiency ratio (PER) and feed efficiency ratio (FER) in Sprague Dawley rats in comparison to  peanut based Plumpy’nut and casein as standard. The proximate analysis of novel RUTF showed that it contains 97.9% dry matter, whereas crude fat, crude protein, crude fiber and nitrogen free extract were 31.33%, 12.4%, 2.17% and 50.6%, respectively and was statistically similar to Plumpy’nut. The protein quality experiments showed that the TD of RUTF, Plumpy’nut and casein was 83.78, 86.98 and 93.16, NPU was 73.54, 77.42 and 86.58, BV was 87.77, 89.01 and 92.98,  respectively, and these parameters of RUTF and Plumpy’nut were statistically similar to each other but lower than casein. The PER was statistically different for all treatments and was 1.92, 2.13 and 2.82 for RUTF, Plumpy’nut and casein, respectively. The FER of RUTF (0.228) was statistically higher than Plumpy’nut (0.193) but lower than casein (0.275). It can be concluded that novel indigenous source chickpea based RUTF is similar to Plumpy’nut with respect to nutritional value and protein quality.
Keywords: Chickpea; Malnutrition; Plumpy’nut; RUTF; Therapeutic Food